2003
DOI: 10.1007/s00125-003-1157-x
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-DR phenotype modulates the humoral immune response to enterovirus antigens

Abstract: Aims/hypothesis. Enterovirus infections are among the environmental risk factors potentially contributing to the pathogenesis of Type 1 diabetes. The aim of this study was to evaluate virus-host interaction by analysing the enterovirus antibody levels in subjects carrying different HLA-DR alleles associated with either increased or decreased risk of Type 1 diabetes. Methods. Antibodies against coxsackievirus B4 were measured to study immune responses induced by natural enterovirus infections and against poliov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
3
33
1
Order By: Relevance
“…The two different studies conducted in these two different counties, one in the very South of Sweden (present study) and the other in the northern part of the country therefore showed comparable results. Furthermore, the new finding that high level LVAb were associated with the T1D high risk HLA DQ2/8, 8/8, and 8/X genotypes support the well-known association between HLA and the immune response to virus (33). The association is likely to be explained by HLA-DQ8 as there was no association between HLA-DQ 2/2 or 2/X (X is not 8) subjects.…”
Section: Discussionsupporting
confidence: 65%
“…The two different studies conducted in these two different counties, one in the very South of Sweden (present study) and the other in the northern part of the country therefore showed comparable results. Furthermore, the new finding that high level LVAb were associated with the T1D high risk HLA DQ2/8, 8/8, and 8/X genotypes support the well-known association between HLA and the immune response to virus (33). The association is likely to be explained by HLA-DQ8 as there was no association between HLA-DQ 2/2 or 2/X (X is not 8) subjects.…”
Section: Discussionsupporting
confidence: 65%
“…These HLA allele combinations vary between countries, and high-risk combinations may be more prevalent in countries with a high diabetes incidence, thus contributing to the international variation in diabetes incidence [45]. However, the difference observed between high-and low-incidence countries is opposite to the expected one if HLA risk genes were involved, as a strong antibody response to enteroviruses is associated with HLA risk alleles for type 1 diabetes [44]. The present observation that Finnish women had a stronger antibody response when positive in the neutralisation assay may reflect the effect of HLA, even though other factors such as a low level of background enterovirus infection in the Finnish population may also play a role, leading to a higher response to the infection.…”
Section: Resultsmentioning
confidence: 99%
“…In the international comparisons, the distribution of HLA risk alleles for type 1 diabetes is one possible source of bias as HLA can modulate the immune response to enterovirus antigens [42][43][44]. These HLA allele combinations vary between countries, and high-risk combinations may be more prevalent in countries with a high diabetes incidence, thus contributing to the international variation in diabetes incidence [45].…”
Section: Resultsmentioning
confidence: 99%
“…A Finnish study indicated that the increased relative risk associated with childhood milk consumption may be higher among siblings of affected children carrying HLA class II genotypes conferring strong or moderate disease susceptibility than among those with low or decreased risk genotypes (63). HLA risk alleles for type 1 diabetes have also been linked to the appearance of autoantibodies subsequent to enterovirus infections (37) and to increased immune responsiveness to enterovirus antigens (90). Another consideration that has to be taken into account is that there may be interactions between two or more environmental factors.…”
Section: Discussionmentioning
confidence: 99%